2019
DOI: 10.1002/chem.201806122
|View full text |Cite
|
Sign up to set email alerts
|

Halogen‐Mediated Membrane Transport: An Efficient Strategy for the Enhancement of Cellular Uptake of Synthetic Molecules

Abstract: The poor uptake of fluorescent probesa nd therapeutics by mammalian cells is am ajor concern in biological applicationsr anging from fluorescencei maging to drug delivery in living cells. Although gaseous molecules such as oxygen and carbon dioxide, hydrophobic substances such as benzene, and small polar but uncharged molecules such as water ande thanolc an cross the cell plasma membrane by simple passived iffusion, many synthetic as well as biological molecules require specific membrane transporters and chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Mugesh et al. reported that the introduction of either a 2,6‐diiodoanisole or 2,6‐diiodophenol group into various fluorophores dramatically promoted their cellular uptake with the assistance of a thyroid hormone cell membrane transporter (MCT‐8) . Interestingly, no significant difference in cellular uptake of PS Se‐H , PS Se‐Br , and PS Se‐I was observed (see Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…Mugesh et al. reported that the introduction of either a 2,6‐diiodoanisole or 2,6‐diiodophenol group into various fluorophores dramatically promoted their cellular uptake with the assistance of a thyroid hormone cell membrane transporter (MCT‐8) . Interestingly, no significant difference in cellular uptake of PS Se‐H , PS Se‐Br , and PS Se‐I was observed (see Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the fluorescent properties of compounds 6 – 11 conatining a −CH 2 −CH 2 − moiety between the phenyl and naphthalimide groups have been investigated (Figure ). Although there was a decrease in the fluorescence upon introduction of bromine and iodine atoms due to heavy‐atom effect, the good fluorescence intensities observed for compounds 6 – 11 indicated that compounds 6 – 11 are suitable for the cellular uptake studies . As expected, a very weak fluorescence was observed for the cells treated with compounds 6 and 7 , and a remarkable enhancement of the fluorescence was observed for cells treated with the diiodo derivative 8 .…”
Section: Cellular Uptake Of Halogen Compoundsmentioning
confidence: 51%
“…A similar increase in the cellular uptake was observed on moving from 9 (16 %) and 10 (38 %) to the diiodo derivative 11 (97 %), although the replacement of the −NH 2 group with an −NMe 2 group only marginally improved the cellular uptake. Further studies with other related naphthalimide‐based compounds 12 – 19 revealed that the uptake of iodine‐containing compounds 15 and 19 is significantly higher than that of their analogues 12 – 14 and 16 – 18 , respectively, although the position of the 2,6‐diiodoanisole in 15 and 19 is different from that of compound 5 (Figure D, E) . These observations indicate that the diiodoanisole and not the napthalimide moiety may act as a recognition unit for the membrane transport.…”
Section: Cellular Uptake Of Halogen Compoundsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is surprising since halogen atoms, present in c.a. 25% of marketed drugs and being even more prevalent in earlier stages of drug discovery and development processes, 39 have traditionally been employed in rational drug design to improve the pharmacokinetic profile of lead molecules, namely to enhance passive diffusion across membranes 40 or, as recently shown, to increase the receptor-mediated uptake of small fluorescent molecules 41,42 or proteins 43 by mammalian cells. 44 Also, iodination of polymers increases their cellular uptake by plant cells, an effect attributed to HaBs.…”
Section: Introductionmentioning
confidence: 99%